Investigation of TiCr Hydrogen Storage Alloy - Pedicini, R.; Gatto, I.; Passalacqua, E.; Biffi, C.A.; Coduri, M.; Tuissi, A. (Journal of Technology Innovations in Renewable Energy, 2018)
A new reversible hydrogen storage material, based on TiCr metal alloy, is proposed. Cr and Ti were mixed and melted in a final atomic ratio of 1,78. Chemical-physical characterisations, in terms of XRD and SEM-EDX, were performed. The quantification of Laves phases was performed through Rietveld refinements. The atomic Cr/Ti ratio was determined by EDX analysis and 1,71 was obtained. The H2 sorption/desorption measurements by Sievert apparatus were carried out. After different tests varying temperature and pressure, a protocol measurement was established; and a H2 sorption value of 0,4 wt% at 200 °C/10 bar with a fast kinetic at 5 bar (Dwt% of about 0,3 wt%) were obtained. Hydrogen desorption measurements performed in the same conditions of T confirmed a totally reversible trend. A confirm of metal hydride formation was recorded by XRD, in fact, comparing X-Ray patterns before and after volumetric tests a notable difference was recorded.